ANALYSIS OF IMPLEMENTATION OF LOCAL LABOR RECRUITMENT IN JOUMPA UNIT AS A FORM OF SOCIAL RESPONSIBILITY OF PT GAPURA ANGKASA BRANCH DENPASAR - Renaldi, I Putu Alit; Abiyasa, Agus Putu (LPPM Univ. Ibn Khaldun Bogor, 2023)
JOUMPA has the meaning